Role of Fracture Risk Assessment Tool and Bone Turnover Markers in Predicting All-Cause and Cardiovascular Mortality in Hemodialysis Patients - Wu, Pei-Yu; Chen, Szu-Chia; Lin, Yi-Ching; Chen, Po-Chih; Chung, Wei-Shiuan; Huang, Ya-Chin; Wu, Ping-Hsun; Tsai, Yi-Chun; Huang, Jiun-Chi; Chiu, Yi-Wen; Chang, Jer-Ming (Frontiers in Medicine, 2022)
Background: Fracture Risk Assessment Tool (FRAX) and bone turnover markers (BTMs) predict fractures in the general population. However, the role of FRAX and BTMs in predicting mortality remains uncertain in hemodialysis (HD) patients. Methods: One hundred and sixty-four HD patients stratified by low or high risk of 10-year fracture probability using FRAX. High risk of fracture was defined as 10-year probability of hip fracture ≥3% or major osteoporotic fracture ≥20%. The association of high risk of fracture and BTMs with all-cause mortality and cardiovascular (CV) mortality were evaluated using multivariate-adjusted Cox regression analysis. Results: Eighty-five (51.8%) patients were classified as high risk of fracture based on FRAX among 164 HD patients. During a mean follow-up period of 3.5±1.0 years, there were 39 all-cause deaths and 23 CV deaths. In multivariate-adjusted Cox regression, high risk of fracture based on FRAX was independently associated with all-cause mortality (hazard ratio [HR]: 2.493, 95% confidence interval [CI]: 1.026–6.056, p=0.044) but not with CV mortality (HR: 2.129, 95% CI: 0.677–6.700, p=0.196). There were no associations between BTMs and mortality risk. Furthermore, lower geriatric nutritional risk index (GNRI) was significantly associated with increased CV mortality (HR: 0.888, 95% CI: 0.802–0.983, p=0.022) after adjusting by confounding variables. Conclusion: High risk of fracture using FRAX was an independent predictor of all-cause mortality in patients undergoing HD. FRAX, rather than BTMs, has an important role of prognostic significance in HD patients.